Factors Influencing Purchase Intention in Affecting Purchase Decision: A Study of E-commerce Customer in Greater Jakarta - Komalasari, Farida; Christianto, Antonny; Ganiarto, Eko (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2021)
This study aims to identify factors influencing purchase intention in affecting purchase decision of e-commerce customers in Greater Jakarta. This research employs survey by distributing questionnaires to 300 respondents in Greater Jakarta aged between 19 – 39 years old, who were selected by purposive snowball sampling technique. The data collected were analyzed by Structural Equation Model (SEM). This research reveals that perceived risk has a negative impact on purchase intention, while perceived benefit, trust, and brand image have a positive impact on purchase intention. Meanwhile, purchase intention has a positive impact on purchase decision for e-commerce customers. It is important to note that perceived benefit, trust, and brand image are strong drivers of purchase intention, which affect purchase decision. E-commerce companies may develop strategies to increase customer purchase decision by managing those variables